Teaching approaches in ESL classroom: A case study / Nur Diyana Mohd Razali - Mohd Razali, Nur Diyana (2014)
The aim of this study is to find out the expectations from the lecturers and students in teaching approaches used in ESL classroom. The study is conducted at Management & Science University (MSU), a private university in Malaysia. It explores 4 themes: the present teaching approaches that the lecturers are using in ESL classroom, preferred teaching approaches, as well as, students' preferred Teaching Approaches and correlations between lecturers' preferred and students' preferred teaching approaches in teaching/learning in ESL classroom. The survey and interview methods are used to achieve the aim of this study. The number of participants in this study is 124 (120 students and 4 lecturers).The findings of both surveys are correlated to their preferred ways of teaching and learning English as a second language in ESL classroom. The findings reveal that various teaching methods are well practiced by lecturers in teaching ESL classroom in a private university and they are aware of the needs of the students despite the challenges to cope with the target language teaching by looking at the four skills of learning a language (a) Listening (b) Speaking (c) Reading and (d) Writing. It is important for the lecturers to identify and to pay attention to the student's preferences as well as what the lecturers' have been practicing to avoid any misunderstanding and to maintain or improve the quality of the teaching- learning experience in higher education. It also will help the lecturers to be more creative as well as innovative in using various teaching approaches in teaching English as a Second Language. v